Anisotropic patterns of nanospikes induces anti-biofouling and mechano-bactericidal effects of titanium nanosurfaces with electrical cue - Eiji Kato; Masahiro Yamada; Eitoyo Kokubu; Hiroshi Egusa; Kazuyuki Ishihara (Materials Today Bio)
Anti-microbial nanopatterns have attracted considerable attention; however, its principle is not yet fully understood, particularly for inorganic nanopatterns. Titanium nanosurfaces with dense and anisotropically patterned nanospikes regulate biological functions with multiple physical stimulations, which may be because of the nanopattern-induced alternation of surface physical properties. This study aimed to determine the antimicrobial capability of titanium nanosurfaces and their mechanisms. Two types of alkali-etched titanium nanosurfaces with isotropically or anisotropically patterned nanospikes had markedly denser surface protrusions, greater superhydrophilicity, and greater negative charge than machined or micro-roughened titanium surfaces. The crystallographic properties of anisotropic titanium nanosurfaces were similar to those of isotropic nanosurfaces, but markedly higher in electric reactivity at nanoscale. The maximum value of the contact potential difference on titanium surfaces was significantly correlated with the product of the density and anisotropy in the distribution pattern of surface protrusions. Isotropic titanium nanosurfaces did not inhibit the attachment of gram-positive cocci, such as Staphylococcus aureus, whereas anisotropic titanium nanosurfaces substantially inhibited gram-positive cocci attachment. Most gram-negative bacilli, Escherichia coli, died via swelling of the cell body on anisotropic titanium nanosurfaces within 6 h of incubation, in contrast to other titanium surfaces where most of the cells did not lose viability or undergo morphological changes. The extent of cell swelling was positively correlated with the electric reactivity of the titanium surfaces. Titanium nanosurfaces with anisotropically patterned dense nanospikes exerted anti-biofouling or mechano-bactericidal effects on gram-positive or negative bacteria with electrical cue induced by the anisotropy of the nanospike patterns.